History and status quo of higher public health education in China - Hui Jin; Guoqiang Dong; Liling Zou; Xiaobing Shen; Dongmei Li (Frontiers Media S.A., 2020)
Abstract This purpose of the study is to systematically understand the development history and influencing factors of higher public health education in China. We extensively collected the public health education-related literature in China, summarized the general framework, historical origin, and development mode of the existing public health education system, and discussed the potential development tendency. Public health education in China changed with the development of higher medical education and higher education in China. Higher education in China has experienced several large-scale adjustments and enrollment expansions due to different purposes. Therefore, its development stage can be roughly divided into three stages: 1949 to 1976 (period of planned economy), 1977 to late 1998 (period of reform and opening up), and from 1999 to present (period of deepening reform and social transformation). The current public health education in China is influenced by many models, such as the American model, European model (especially the former Soviet Union), and ideological and political education model. It still faces some problems or challenges, such as bachelor's programs, Master of Public Health, social identity, professional accreditation, and broader public health. In fact, it is necessary to establish an important education system based on the concept of modern public health, beyond the existing medical education system, in order to meet the challenges and needs of public health in the twenty-first century.